Дослідження впливу конструктивних чинників на ефективність роботи магнітних ловильних пристроїв - Романишин, Л.І.; Романишин, Т.Л. (Породоразрушающий и металлообрабатывающий инструмент – техника и технология его изготовления и применения, 2010)
The critical overview of the magnetic tools for bottom hole cleaning was given as well as the
exploitation requirements for this type of equipment were studied. New construction of magnetic
tool for metal cleaning-up-jobs in the process of drilling, blowouts and well reconstruction has
been described.